Electrophysiological Properties of Octopus Neurons of the Cat Cochlear Nucleus: an In Vitro Study - Bal, Ramazan; Baydas, Giyasettin (Springer, 2009)
Electrophysiological studies from mice in vitro have suggested that octopus cells of the mammalian ventral cochlear nucleus (VCN) are anatomically and biophysically specialized for detecting the coincident firing of a population of auditory nerve fibers. Recordings from cats in vivo have shown that octopus cells fire rapidly and with exceptional temporal precision as they convey the timing of that coincidence to higher auditory centers. The current study addresses the question whether the biophysical properties of octopus cells that have until now been examined only in mice, are shared by octopus cells in cats. Whole-cell patch-clamp recordings confirm that octopus cells in brain slices from kittens share the anatomical and biophysical features of octopus cells in mice. As in mice, octopus cells in kittens have large cell bodies and thick dendrites that extend in one direction. Voltage changes produced by depolarizing and hyperpolarizing current injection were small and rapid. Input resistances and membrane time constants in octopus cells of 16-day-old kittens were 15.8 +/- 1.5 M Omega (n = 16) and 1.28 +/- 0.3 ms (n = 16), respectively. Octopus cells fired only a single action potential at the onset of a depolarizing current pulse; suprathreshold stimuli were greater than 1.8 nA. A tetrodotoxin (TTX)-sensitive sodium conductance (g (Na)) was responsible for the generation of the action potentials. Octopus cells displayed outward rectification that lasted for the duration of the depolarizing pulses. Hyperpolarizations produced by the injection of current exhibited a depolarizing sag of the membrane potential toward the resting value. A 4-aminopyridine (4-AP) and alpha-dendrotoxin (alpha-DTX)-sensitive, low-voltage-activated potassium conductance (g (KL)) and a ZD7288-sensitive, mixed-cation conductance (g (h)) were partially activated at rest, giving the octopus cells low input resistances and, as a consequence, brief time constants. In 7-day-old kittens, action potentials were taller and broader, input resistances higher, and both inward and outward rectification was weaker than in 16-day-old kittens. Also as in mice, stellate cells of the VCN fired trains of action potentials with constant interspike intervals when they were depolarized (n = 10) and bushy cells of the VCN fired only a single action potential at the onset of depolarizations (n = 6). In conclusion, the similarity of octopus cells in mice and kittens suggests that the anatomical and biophysical specializations that allow octopus cells to detect and convey synchronous firing among auditory nerve fibers are common to all mammals.
Keywords: auditory pathways; cochlear nucleus; octopus cell; patch clamp; cat